ADOLESCENT CHILD PARENTING SKILLS THROUGH PHYSICAL ASPECT OF STUDY IN MUSLIM FAMILIES IN MALAYSIA AND INDONESIA - Nurmatias, Windayani; Akbar, Rizal; Raffar, Izzah Nur Aida Zur; Nurmatias, Faizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Adolescents represent a strategic demographic group undergoing significant biological, psychological, and social transformations, requiring appropriate parenting approaches to shape healthy lifestyle behaviors. Globally, there are 1.8 billion adolescents, while in Indonesia the number reaches 44.29 million; however, various studies indicate that many still face issues such as poor personal hygiene, insufficient physical activity, irregular sleep patterns, and unbalanced diets. This study aims to explore parental skills in fostering the physical aspects of adolescents based on Islamic values and Malay culture in Indonesia and Malaysia. A quantitative survey method was employed, using online questionnaires distributed to 429 adolescents in Malaysia and 94 adolescents in Indonesia. Data were analyzed descriptively using SPSS to obtain frequency distributions, means, and standard deviations. The results show that parental physical care skills are at a high level, with average scores ranging from 3.26 to 3.76. Assessed aspects include grooming according to proper gender identity, personal hygiene, proper aurah covering, engaging in healthy leisure activities, adequate sleep, practicing Islamic eating and drinking etiquette, consuming balanced and sunnah-based diets, caring for health, and administering necessary medication during illness. The integration of religious values and local Malay wisdom has been proven to strengthen the formation of healthy, disciplined, and well-mannered physical habits among adolescents. This study concludes that parents play a crucial role as role models and guides for a healthy lifestyle grounded in Islamic and local cultural values. It is recommended that family education programs in Malay communities strengthen literacy on adolescent physical care aligned with religious teachings and cultural traditions to address modern adolescent health challenges